A Legal Analysis of Citizens’ Legal Protection Against Adverse Administrative Decisions from the Perspective of Administrative Courts - Revameila Susanti; Zulfi Ashari; Ahmad Ramdani; Nila Syahfitri Hasibuan; Tierra Kresna; Taufiq Alamsyah (Anthroposia: Journal of Social and Human Development, 2026)
The increasing complexity of public administration and the expansion of digital governance have intensified the need for effective legal protection against adverse administrative decisions. This study examines the juridical framework of citizens’ legal protection within the Administrative Court system in Indonesia. The research employs a normative legal method based on a doctrinal approach using statutory, conceptual, and doctrinal analysis. Primary legal materials consist of the 1945 Constitution, the State Administrative Court Law, the Government Administration Law, Government Regulation Number 48 of 2016, and Supreme Court Regulation Number 1 of 2019. These materials are complemented by scholarly literature concerning administrative law, judicial review, and administrative accountability. The findings indicate that legal standing constitutes the principal mechanism enabling citizens to challenge governmental actions before Administrative Courts. Judicial review has evolved beyond formal legality assessment toward broader scrutiny of governmental conduct and administrative accountability. The study also reveals that the effectiveness of legal protection depends not only on judicial accessibility and legality review but also on the implementation of court decisions and institutional compliance by administrative authorities. Administrative Courts therefore function as essential instruments for safeguarding citizens’ rights, maintaining legality, strengthening accountability, and reinforcing the rule of law within contemporary governance.